FRI0388 Effects of Blisibimod on Serum Immunoglobulins and Infection Risk in Patients with Systemic Lupus Erythematosus from the Placebo-Controlled PEARL-SC and Open-Label Extension Studies. (10th June 2014) - Richard, F.A.; Scheinberg, M.A.; Thomas, M.; Chu, A.D.; Martin, R.S.; Hislop, C.; Petri, M.
Abstract : Background: Blisibimod, a peptibody that inhibits B-cell activating factor (BAFF), was previously found [1] to be safe, efficacious and well-tolerated in patients with systemic lupus erythematosus (SLE) that participated in a Phase 2 randomized, double-blind, placebo-controlled trial (PEARL-SC, NCT01162681 ). Objectives: To evaluate the effects of long-term exposure to blisibimod on IgG, IgM and infection risk and white blood cell counts in patients with SLE during the PEARL-SC and the ensuing open-label extension (OLE) study (NCT01305746 ). Methods: 547 SLE patients with anti-double-stranded DNA or anti-nuclear antibodies >1:80 and SELENA-SLEDAI score ≥6 at baseline were enrolled into the PEARL-SC study, and randomized 1:1 to receive placebo or blisibimod administered at 1 of 3 dose levels. In the PEARL-SC study, subjects received blinded study drug for 24 to 52 weeks (with a median of 37 weeks). A total of 382 subjects enrolled in the OLE study and received blisibimod. The efficacy, safety and tolerability of blisibimod in the combined studies are reported here upto the time of the interim analysis of the OLE study in March 2013. Results: Significant reductions in peripheral B cells, IgG and IgM occured in patients in the pooled blisibimod group compared with placebo from Week 8 through Week 52 in the PEARL-SC study (percent changes with blisibimod vs placebo in IgG= -14.1% vs -3.9%, and IgM= -34.6% vs -9.3%, p≤0.003, N=94 at Week 52). IgG and IgM levels continued to be lower compared with pre-treatment levels through Week 80 (changes in IgG= -10.7%, IgM= -34.6%, N=31). There was no difference between treatments in the numbers of subjects reporting infections: placebo 62.0% and blisibimod 58.2%. Furthermore, the mean concentrations of IgG in patients who reported infections were similar between the pooled placebo group (14.6-16.2 g/L) and the pooled blisibimod group (12.9-16.6 g/L). Finally, no effects of blisibimod were observed on peripheral counts of white blood cells including monocytes, lymphocytes, and neutrophils compared with placebo in the PEARL-SC study or over the course of longer-term open-label dosing. Blisibimod was safe and well-tolerated at all dose levels with no meaningful imbalances in serious adverse events in the PEARL-SC study with the exception of injection site reactions (200mg QW blisibimod=15%, matched placebo=7%). During the placebo-controlled study, critically low IgG levels (<4g/L) were observed in 1/280 subjects in blisibimod group compared with 0/266 subjects on placebo. Blisibimod was also safe and well-tolerated in the open label extension study. At the time of the interim analysis serious adverse events were reported in 7 patients, of whom 2 (1.5%) reported serious infections. Conclusions: In patients with SLE, blisibimod induces pharmacological effects on immunoglobulin production that are consistent with a BAFF-mediated inhibition without adversely impacting the risk of infection. Clinical studies with blisibimod in patients with SLE and IgA nephropathy are currently enrolling. References: Furie RA, Scheinberg MA, Leon G, et al. Arthritis Rheum. 2012;64(12):4169. Disclosure of Interest: F. Richard Consultant for: Anthera Pharmaceuticals, M. Scheinberg: None declared, M. Thomas: None declared, A. Chu: None declared, R. Martin Shareholder of: Anthera Pharmaceuticals, Employee of: Anthera Pharmaceuticals, C. Hislop Shareholder of: Anthera Pharmaceuticals, Employee of: Anthera Pharmaceuticals, M. Petri Consultant for: Anthera Pharmaceuticals DOI: 10.1136/annrheumdis-2014-eular.2261